AN ADVANCED REVIEW ON DIAGNOSIS AND TREATMENT AND EXTRA-INTESTINAL MANIFESTATIONS ASSOCIATED WITH INFLAMMATORY BOWEL DISEASE - Sharma, Deep; Rana, Rekha; Thakur, Kiran; Priyanka (Journal of Biomedical and Pharmaceutical Research, 2021)
Inflammatory Bowel Diseases are mainly a group of bowel disorders which are generally associated with chronic inflammation of the intestinal tract due to the reason of an imbalance in the presence of the intestinal microbiota. Inflammatory bowel disease can have two different types based on their clinical pathology which are mainly Crohn’s Disease and Ulcerative Colitis. Both of these clinical sub-types are most likely to be focussed among all of the inflammatory bowel diseases due to their increasing risk of incidence as well as associated difficulties in their treatment. However, the main cause of inflammatory bowel disease has not been cleared till the date but from last three decades, there is a hub of researchnes being going on to get a clear idea about the cause of disease. Among these studies most of researchers have found the role of Nucleotide Oligomerization Domain 2 genes in the pathophysiology of disease. For the treatment of ulcerative colitis, there are severalapproaches available, based on the severity of the disease. Aminosalicylates are used to treat mild disease, use of corticosteroids is the effective treatment in the moderate case whereas use of cyclosporine in severe disease. In Crohn’s disease, drug choices are dependent on both location and behavior ofthe disease. Nowadays, the advanced treatments have been included such as use of monoclonal antibodiesor fusion proteins including anti-TNF drugs as biological therapy of disease. Also the post treatment remission of this disease makes it more complicated to be cured.